Somatostatin alters beta-adrenergic receptor-effector coupling in cultured rat astrocytes. - Niehoff, D L (1985)
The neuropeptide somatostatin potentiates beta-adrenergic receptor-mediated cAMP formation in astrocytes derived from neonatal rat cortex but does not affect cAMP levels by itself. beta-Adrenergic receptors in these cells can be specifically labeled with the high affinity antagonist [125I] cyanopindolol ([125I]CYP). In addition, astrocytes display both high and low affinity binding sites for the agonist isoproterenol, which are thought to represent receptors which are coupled or uncoupled, respectively, to the guanine nucleotide regulatory protein. We find that somatostatin does not modify beta-receptor density, nor receptor affinity for either the antagonist ([125I]CYP) or for the agonist isoproterenol. In the presence of the guanine nucleotide analogue, Gpp(NH)p, only low affinity (uncoupled) displacement of [125I]CYP binding by isoproterenol is observed. However, somatostatin (1 microM), when added to the cells together with Gpp(NH)p, prevents the nucleotide-induced loss of the high affinity (coupled) component of agonist displacement. This result suggests that somatostatin increases noradrenaline-induced cAMP production by enhancing coupling between the beta-receptor and the stimulatory guanine nucleotide regulatory protein.